The fine-scale genetic structure of the malaria vectors Anopheles funestus and Anopheles gambiae (Diptera: Culicidae) in the north-eastern part of Tanzania. (17th August 2016) - Gélin, P.; Magalon, H.; Drakeley, C.; Maxwell, C.; Magesa, S.; Takken, W.; Boëte, C.
Abstract: Understanding the impact of altitude and ecological heterogeneity at a fine scale on the populations of malaria vectors is essential to better understand and anticipate eventual epidemiological changes. It could help to evaluate the spread of alleles conferring resistance to insecticides and also determine any increased entomological risk of transmission in highlands due to global warming. We used microsatellite markers to measure the effect of altitude and distance on the population genetic structure of Anopheles funestus and Anopheles gambiae s.s . in the Muheza area in the north-eastern part of Tanzania (seven loci for each species). Our analysis reveals strong gene flow between the different populations of An. funestus from lowland and highland areas, as well as between populations of An. gambiae sampled in the lowland area. These results highlight for An. funestus the absence of a significant spatial subpopulation structuring at small-scale, despite a steep ecological and altitudinal cline. Our findings are important in the understanding of the possible spread of alleles conferring insecticide resistance through mosquito populations. Such information is essential for vector control programmes to avoid the rapid spread and fixation of resistance in mosquito populations.